ANALYSIS OF LIVELIHOOD SECURITY STATUS FOR WOMEN GROUNDNUT SEED PRODUCERS IN JIGAWA, KANO AND KEBBI STATES, NIGERIA - Abubakar*, A.A.; Ahmed, B.; Yusuf, O.; Yusuf, S.; Njiforti, P.P.; Bello, B. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study was aim to comparatively analyse the livelihood security status for women groundnut seed producers in Jigawa, Kano and Kebbi States, Nigeria. A multistage sampling technique was used to sample 180 women groundnut seed producer across the three States studied. Primary data were collected through face-to-face interviews with the use of semi-structure questionnaire. The analytical techniques used to achieve the stated objectives of the study were descriptive statistics and livelihood security index. The findings of the study revealed that the composite index score of the overall economic security of women groundnut seed producers in Jigawa (0.5506) and Kebbi States (0.5547) were marginally lower than the score of Kano State (0.6730). The study also revealed that the composite index score of the overall educational security of the women groundnut seed producers in Jigawa (0.1552) and Kebbi (0.1611) States was found to be more vulnerable than Kano State (0.2342). Likewise, the findings of the study further revealed that the composite index score of the overall food security of the women groundnut seed producers in Jigawa (0.5173) and Kebbi (0.5116) States was found to be more vulnerable to food insecurity compare to Kano State (0.5284) respectively. In a related development, the findings of the study also shows that the overall score of the social security status of the women groundnut seed producers in Jigawa (0.5148), Kano (0.5978) and Kebbi (0.5335) States were greater than the mid-value in the overall scale of 0-1 points across the three States. Finally, the findings of the study shows that the overall livelihood securities is highest among women groundnut seed producers in Kano State (0.4539) followed by those at Jigawa State (0.3909) with the lowest found in Kebbi State (0.3874). Therefore, the overall values shows that livelihood securities of women groundnut seed producers across the States are quite low. The study recommends that the women groundnut seed producer should be encourage to diversifying their agricultural production system to achieve food self-sufficiency and enhance family income. The study also recommends that the government should increase economic opportunities for the women groundnut seed producers, in the two States for improving upon their economic security status.